Perceived level of assertiveness and self-esteem of nurse interns in Enugu Nigeria - Ifeoma F. Ndubuisi; Ijeoma L. Okoronkwo; Ada C. Nwaneri; Ijeoma Maduakolam; Chijioke O. Nwodoh; Chisom Mbadugha (International Journal of Africa Nursing Sciences)
Background: Assertiveness and high self esteem form the most important behavioural skills for nurses in the workplace, especially to build effective team relationships and to provide quality nursing care. Material and methods: A descriptive cross-sectional study involving ninety-two (92) interns employed in tertiary institutions. Two standardised instruments were used for data collection: Rathus Assertiveness Schedule and Rosenberg Self-Esteem scale. Data were analysed using descriptive and inferential statistics. Results: Majority of the interns have moderate level of self-esteem (55.5). Findings revealed highest scores on self-esteem items; they felt that they had a number of good qualities (3.5 ± 0.8); felt satisfied with themselves (3.5 ± 0.7); could do things as well as most other people (3.4 ± 0.8). Level of assertiveness of the respondents was low 22.2. Non-assertiveness was observed in stating that people took advantage of them (−0.4 ± 2.2); avoid hurting other people’s feelings even when they feel injured (2.0 ± 1.8); not been able to say anything at times (1.8 ± 1.9) and avoiding asking questions for fear of sounding stupid (1.8 ± 2.3). There was no significant association between the level of self-esteem of the nurse interns and their level of assertiveness (x2 = 0.073 and P = 0.787). Conclusion: Nurse interns in Nigeria currently have relative low level of assertiveness, however their level of self esteem is moderately high. Improving these behavioural skills will improve the quality of care rendered by interns therefore these concepts should constitute an integral part of the basic undergraduate nursing courses.